Voltage Regulation Using STATCOM with PI and Adaptive PI Controls - Felix Stephen, S; I. Jacob Raglend, Dr (International Journal of Engineering and Technology, 2018)
In power systems, voltage instability problems occur due to its continuous demand in heavily loaded networks. So it is essential to stabilize the voltage levels in power systems. The stabilization of power systems can be improved by Flexible Alternating Current Transmission System (FACTS) devices. One of the FACTS devices named Static Synchronous Compensator (STATCOM) injects the compensating current in phase quadrature with line voltage and replicate as inductive reactance to produce capacitive power for the AC grid or as capacitive reactance to draw inductive power from the AC grid for controlling power flow in the line. This paper proposes Adaptive PI control over conventional PI that normally self-adjusts the controller gains under disturbances and helps in improving the performance and attaining a preferred response, irrespective of the change of working conditions. The work is implemented under MATLAB/SIMULINK environment. This method performs more efficient than the original PI with fixed control gains and also improves the system response speed consistently.Â Â